Haenszel’s standardized coefficient of lost years of life: a comparison with the standardized coefficient of general mortality with regard to its use as a health level indicator for populations - Juliano, Yára; Novo, Neil Ferreira; Goihman, Samuel; Paiva, Elias Rodrigues de; Leser, Walter (Revista de Saúde Pública, 1987)
The Lost Years of Life Rate (LYLR), proposed by Haenszel in 1950, but since then seldom mentioned in literature, was studied. By using reliable populational data from various countries, and from regions of the State of S.Paulo, they showed that: a) It is convenient to employ 75 years as the age limit for the calculation of the LYLR, as well as a ten-year interval for the age classes that follow the first and second ones (less than 1, and 1 to 4); b) by comparing the ranking of countries and regions, in accordance with their LYLR and by the Standardized mortality rate (SMR), with the corresponding ranking using Novo's comprehensive Indicator (Z) as a parameter, they verified that the discrepancy was smaller in the first case; c) variations in time, of both coefficients, in the countries studied, calculated by the annual variation rate (AVR), were better expressed by LYLR than by SMR; d) using the Infant mortality rate (IMR) as a parameter, the discrepancies in the ordering of AYR, based on LYLR, were significantly smaller than those based on SMR. It was concluded that the LYLR can, with advantage, replace the SMR.